2015
DOI: 10.1021/acs.jpcc.5b07961
|View full text |Cite
|
Sign up to set email alerts
|

Topological Insulating Phases in Two-Dimensional Bismuth-Containing Single Layers Preserved by Hydrogenation

Abstract: Two-dimensional (2D) binary XBi compounds, where X belongs to group III elements (B, Al, Ga, and In), in a buckled honeycomb structure may originate sizable gap Z2 topological insulators (TIs). These are characterized by exhibiting single band inversion at the Γ point as well as nontrivial edge states in their corresponding nanori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
98
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 34 publications
8
98
0
1
Order By: Relevance
“…This trend agrees with present findings. Band gap values calculated by Freitas et al [30] using PBE with and without SOC agree with the present values.…”
Section: Electronic Structuresupporting
confidence: 91%
See 1 more Smart Citation
“…This trend agrees with present findings. Band gap values calculated by Freitas et al [30] using PBE with and without SOC agree with the present values.…”
Section: Electronic Structuresupporting
confidence: 91%
“…The effects of strain and electric field on the electronic structure of a single-layer A7 structure are investigated to show that the structure is a robust 2D topological insulator against strain and electrical field [27]. In addition, the electronic properties of XBi binary compound (X = B, Al, Ga, and In) and hydrogenated Bi(111) films [30] have been explored within the perspective of topological insulator.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the topological insulator property has remained robust under an applied electric field and strain [15]. Not only bare surfaces of Bi, but also the surfaces covered with H have been studied to reveal the effect of adsorbed hydrogen on the topological character of the material [17].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the largest nontrivial bulk gap is 1.08eV found in Bi 2 F 2 monolayer [59,60], which shows that chemical functionalization is a very powerful way to obtain a large nontrivial bulk gap. Using first-principles calculations, some group III-V monolayers were predicted to be QSH insulators with a large bulk gap [24] and it was found that this gap can be enlarged via hydrogenation/functionalization [71][72][73][74][75][76][77][78]. After functionalization, their structures can all be regarded as being composed of RHF.…”
Section: Introductionmentioning
confidence: 99%